TESTING THE ROBUSTNESS OF THEORY OF PLANNED BEHAVIOR IN PREDICTING WOMEN’S INTENTION TO WEAR JILBAB - Sari Winahjoe Siswomihardjo; Sudiyanti Sudiyanti; Bayu Sutikno (Universitas Gadjah Mada, 2018)
For Muslim women, covering aurat has clearly been commanded in Al-Qur’an. Therefore, most Muslim women wear Jilbab to do so. Although Indonesia is the world’s largest Muslim country and in recent years, more fashionable Jilbab designs have been growing in Indonesian Muslim fashion market, yet, not all Muslim women wearing Jilbab. This study examines how well the Theory of Planned Behavior works in predicting Muslim women’s intention to wear Jilbab. This article proposes that Muslim women’s intentions to wear Jilbab are influenced by their attitude, subjective norms, perceived behavioral control, and together with perceived personal outcome. By using purposive sampling method, a representative national sample of 200 Indonesian Muslim women has been participated in a face-to-face survey about this topic. The findings confirmed the robustness of the Theory of Planned Behavior by indicating that both attitude and subjective norms significantly brought positive effect in predicting intention. Interestingly, the results demonstrated that perceived personal outcome and perceived behavior control appeared to be ineffective determinants. Therefore, the study result also slightly deteriorated the robustness of the Theory of Planned Behavior in the context of predicting Indonesian Muslim women’s intention to wear Jilbab. We present our findings, suggestions for future research, and potential limitations. The implications of this research for marketing practitioners are also discussed.